Role of Sources Power Man in Success Digital Transformation: An Overview Qualitative to the Model and Framework Planning - Novrizal; Iskandar, Eddy (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
This qualitative literature review explores the critical role of human resources (HR) in the success of digital transformation initiatives. The study highlights that digital transformation extends beyond technological adoption, requiring organizational cultural shifts and process reengineering. HR is pivotal in facilitating these changes through skill development, employee empowerment, and cross-departmental collaboration. Effective leadership and a clear strategic vision are essential to guide organizations through this transformation journey. Structured frameworks are necessary to ensure all elements harmoniously work towards achieving digital transformation goals. Despite providing valuable insights, this study is limited by its reliance on recent literature, potentially overlooking relevant older studies, and its qualitative nature, which may not be generalizable across all industries. Further research is needed to validate these findings across diverse organizational contexts.